Fine structures of a solar type III radio bursts observed with LOFAR - Dabrowski, Bartosz; Wolowska, Aleksandra; Vocks, Christian; Magdalenić, Jasmina; Zhang, Peijin; Flisek, Pawel; Bröse, Malte; Morosan, Diana E.; Krankowski, Andrzej; Fron, Adam; Mann, Gottfried; Zucca, Pietro; et al. (SPRINGER INT PUBL AG, 2025)
We present spectral and imaging LOFAR (LOw-Frequency ARray) observations in the 20 – 40 MHz range of solar radio bursts fne structures, such as fag-like, sail-like, and dot-like that appeared on 8 April 2019. These structures were associated with type III solar radio bursts that occurred in the 40 – 80 MHz band. The mean duration and spectral widths of the fne structures range from 1.0 to 3.4 s and from 0.3 to 0.9 MHz, respectively. Additionally, we investigated the radio images of eight fne structures – two fags, two sails and four dots. This allowed us to determine their emission source sizes, which ranged from 240 to 392 arcmin2, and their frequencies from 25.58 to 39.25 MHz as well as their location. They occurred on the east side of the Sun and were most likely associated with an emerging active region NOAA AR 12738, where a weak B1.7 fare was observed.